Dedicated solar powered charging kit: a system alternative to the solar charging station for single user - Himel, Shafquat Aziz; Datta, Aditi (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.